Effects of Predictive Nursing Intervention among Patients with Acute Stroke - Lina Gong; Chunhong Ruan; Xuan Yang; Wanli Lin (Tehran University of Medical Sciences, 2021)
Background: To explore the effects of predictive nursing intervention among patients with acute stroke. Methods: One hundred and sixty participants were included. They were hospitalized in the Department of Neurology of a third-level first-class hospital in Changsha, Hunan Province, from January to August 2019. They were categorized into control group and intervention group by random number table, with 80 patients in each group. General nursing for patients in Neurology Department was offered to the control group. On the basis of general nursing, predictive nursing intervention was offered to the intervention group. The effectiveness of predictive nursing intervention were evaluated by disparity in neurologic function, movement function, daily life ability and sleep quality before intervention and 2 weeks after intervention. The neurologic function, movement function, daily life ability and sleep quality were evaluated by National Institute of Health acute stroke scale (NIHSS), Fugl-Meyer scale, Barthel indicator, and Pittsburgh sleep quality indicator (PSQI), respectively. Results: There was no significant difference in gender, age, complications and treatment methods between two groups. There was no significant difference in the scores of NIHSS, Fugl-Meyer scale, Barthel indicator, and PSQI before intervention. The scores of NIHSS and PSQI were significantly lower in the intervention group than those in the control group, and the scores of Fugl-Meyer scale and Barthel indicator were significantly higher in the intervention group than those in the control group (P <0.05). Conclusion: Predictive nursing intervention could help improve not only neurologic function, movement function, and daily life ability, but also sleep quality among patients with acute stroke.